2023
DOI: 10.3389/fenrg.2023.1092637
|View full text |Cite
|
Sign up to set email alerts
|

A review on biochar’s effect on soil properties and crop growth

Abstract: Intensive cultivation of agricultural soils causes soil degradation which emphasizes the need for sustainable soil management. Biochar, a pyrolysed carbon rich material has gained great interests among the researchers because of its eco-friendly benefits in addition to soil quality enhancement. Reviews on biochar, mainly confined to its environmental benefits like carbon sequestration and climate change. In this review, we summarize i) the effect of biochar application on soil properties (physical, chemical, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 262 publications
0
3
0
1
Order By: Relevance
“…These characteristics significantly influence the soil properties while using biochar as an amendment in a specific soil. 12 The biochar properties are also influenced by the biochar feedstock (BF) (source of biochar: wood, grain, straw, and waste material) 13 and biochar pyrolysis temperature (BPT) (used during the process of formation of biochar). 14,15 The use of biochar prepared from different feedstocks and BPT showed varying results in improving the acidic soil properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics significantly influence the soil properties while using biochar as an amendment in a specific soil. 12 The biochar properties are also influenced by the biochar feedstock (BF) (source of biochar: wood, grain, straw, and waste material) 13 and biochar pyrolysis temperature (BPT) (used during the process of formation of biochar). 14,15 The use of biochar prepared from different feedstocks and BPT showed varying results in improving the acidic soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of biochar include its physicochemical properties such as biochar pH (BpH), biochar electrical conductivity (BEC), biochar cation exchange capacity (BCEC), biochar total N (BN), biochar total P (BP), biochar total K (BK), biochar ash (BAs), bulk density (BBD), biochar C/N ratio (BC/N), and pore size. These characteristics significantly influence the soil properties while using biochar as an amendment in a specific soil . The biochar properties are also influenced by the biochar feedstock (BF) (source of biochar: wood, grain, straw, and waste material) and biochar pyrolysis temperature (BPT) (used during the process of formation of biochar). , The use of biochar prepared from different feedstocks and BPT showed varying results in improving the acidic soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a carbon-rich and insoluble solid material obtained by high-temperature pyrolysis of agricultural and forestry wastes under anaerobic or anoxic conditions ( Premalatha et al., 2023 ). It primarily comprises carbon (C), hydrogen (H), oxygen (O), nitrogen (N), and other essential plant nutrients such as phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) ( Danesh et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar, which is made from pyrolyzed wastes that have a longer residence period than unpyrolyzed wastes, increases soil fertility by affecting the physiochemical and biological characteristics of the soil [18,19]. Many studies have shown that biochar has a good impact on soil characteristics and crop output [20][21][22]. Depending on the kind, dosage, and soil type, biochar features such as pH, increased surface area, cation exchange capacity, and nutrient content positively influence soil parameters and ultimately improve soil fertility [23].…”
Section: Introductionmentioning
confidence: 99%